2021
DOI: 10.33806/ijaes2000.21.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Palestine in Visual Representation: A Visual Semiotic Analysis of the Nakba

Abstract: Since its de facto creation, Israel has endeavoured to legitimize its existence and mystify the ethnic cleansing it perpetrated in 1948, systematically working to efface historic Palestine from the Arab and global public memory. Visual discourse plays a constitutive role in the construction and preservation of national themes. This paper, a critical discourse analysis of a corpus of visual representations, aimed to examine how visual representation serves to memorialize and reconstruct national themes, and so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have expanded the scope to include Arab media. It should come as no surprise that analyses of Al Jazeera and the Middle East press revealed that their framing prioritize Palestinian experiences and interpretations above Israeli ones (Amaireh, 2024;Majzoub, 2021;Taha, 2017). However, this also highlighted the asymmetry, as Western audiences have far greater exposure to prominent international outlets like CNN, BBC, and major newspapers with documented pro-Israeli leanings (Hearns-Branaman & Bergman, 2022).…”
Section: Media Bias In the Israeli-palestinian Conflictmentioning
confidence: 99%
“…Recent studies have expanded the scope to include Arab media. It should come as no surprise that analyses of Al Jazeera and the Middle East press revealed that their framing prioritize Palestinian experiences and interpretations above Israeli ones (Amaireh, 2024;Majzoub, 2021;Taha, 2017). However, this also highlighted the asymmetry, as Western audiences have far greater exposure to prominent international outlets like CNN, BBC, and major newspapers with documented pro-Israeli leanings (Hearns-Branaman & Bergman, 2022).…”
Section: Media Bias In the Israeli-palestinian Conflictmentioning
confidence: 99%
“…This further led to an increase in L2 N. Pazaer & A. Assaiqeli, Pre-service teachers' views on using English comics to improve pupils' English language skills | 208 reading speed. Indeed, such intersemiotic complementarity, as indicated by Assaiqeli (2021), would have a collocational relationship between the visual and verbal elements of the text that reinforced the message communicated -intersemiotically (verbalvisual intersemiosis).…”
Section: Reading Skillsmentioning
confidence: 99%
“…It can also teach students the importance of deciphering the messages behind an image that may encapsulate and signify a culture depending on the material used. Assaiqeli (2021) demonstrated how Palestinian visual language, for example, works to record and express significant Palestinian national themes, thereby contributing to the preservation of Palestinian national identity and the revival of Palestinian nationalism and national consciousness. This study established that people could transmit sentiments and invoke memory despite historical oblivion just through visual language.…”
Section: Introductionmentioning
confidence: 99%